Enhancing rural teacher competence in Meranti Islands Regency high school basic physics practical curriculum - Saktioto, Saktioto; Defrianto, Defrianto; Rini, Ari Sulistyo; Irawan, Dedi; Agrina, Agrina; Anita, Sofia; Soerbakti, Yan; Rabin, Mohammed Fisal (Universitas Riau, 2024)
Teacher competency standards serve as benchmarks that can be utilised to assess the attributes deemed essential for professional competence in educators. Educators play a crucial and strategic role in the pursuit of national development objectives, particularly within the realm of education. However, the objective of education appears to be a reduction in competency standards at the conclusion of each academic year for specific subjects, particularly in the realm of science and Basic Physics. Consequently, this initiative seeks to inspire educators and students in secondary education to enhance their understanding of the educational process by engaging in the study of science, specifically Basic Physics, utilising appropriate tools and resources. The suggested mode of engagement involves the processes of instruction and education within secondary educational institutions across the Meranti Islands Regency, encompassing SMA, MAN, MTs, and SMP levels. This activity further offers insights into experiments and demonstration tools for educators in the realm of science and Basic Physics, facilitating a comprehension of concepts that range from simple to intricate natural phenomena through accessible demonstration media designed for practical application. In this manner, educators are anticipated to exhibit motivation and enthusiasm throughout the learning process, accompanied by a thorough and nuanced comprehension of the subject matter. To enhance teacher competency standards significantly, ensuring they become more qualified and professional.